AB0008 CLINICAL AND GENETIC FEATURES OF NON-BACTERIAL OSTEOMYELITIS IN RUSSIAN FEDERATION. (June 2019) - Kostik, Mikhail; Makhova, Maria; Suspitsin, Evgeny; Sokolenko, Anna; Zorin, Vyacheslav; Isupova, Eugenia; Magomedova, Shamai; Kostik, Inna; Takayanagi, Hiroshi; Mushkin, Alexander; Imyanitov, Evgeny
Abstract : Background: Chronic non-bacterial osteomyelitis (CNO) is Data about incidence, prevalence and clinical and genetic features of chronic non-bacterial osteomyelitis (CNO) in Russia is scarce. Objectives: The aim of our study was to evaluate clinical and genetic peculiarities of CNO in Russia. Methods: The diagnosis of CNO was made with criteria, proposed by Jansson [1, 2], after the exclusion of other causes of bone disease. Our cohort consists of three main subtypes: i) early-onset (<5 years) CNO (n=22); ii) CNO, associated (n=20) and iii) not associated (n=59) with rheumatic diseases (RD). Targeted next generation sequencing (NGS) analysis of 302 genes related to primary immune defficiency syndromes and autoinflammatory syndromes was performed. Results: We selected a subgroup of the CNO patients having the following features: 1) early disease onset (<5 years); 2) all children were initially diagnosed as having tuberculosis (TB) due to bone morphology findings (granulomatosus, e.g. tuberculosis-like inflammation), but had negative TB culture test; 3) initial treatment with combination of 3-4 anti-MBT drugs during 1-2 years was ineffective, and the patient continued to develop new inflammatory bone foci; 4) patients had very severe clinical (fever and symptomatic arthritis) and radiological signs of disease; 5) all patients were from areas with traditionally high prevalence of consanguinity (table). In the subgroup patients with early onset we performed genetic tests. Rare variants of PID genes were detected in 7/22 (32%) patients. Mutations affecting the genes previously associated with CNO were found only in two patients: one of them carried heterozygous variant IL1RN c.170G>T (p.C57F) and another had IL1RN c.512T>C (p.V171A). No mutation of LPIN2 was revealed. Other detected variants included one pathogenic MEFV p.M694V mutation in heterozygous state and a number of VUS in CD40LG, NLRP12, CR2, NLRP3, IL12B, PLCG2, SH3BP2, CARD14, IRF8, CASP10 and NFKB1A genes. Conclusion: We have found the unique regional subtype of CNO with early-onset in North Caucasus region with at least 10 times higher prevalence. We have not yet seen similar patients in other nationalities of Russia. Mutations in known genes were detected only in a minor fraction of CNO patients from Dagestan and Chechnya. This work supported by the Russian Foundation for Basic Research (grant No 18-515-57001) and by Japan Medical Research Foundation (grant No 18jmrf001). References: [1] Jansson AF, Müller TH, Gliera L, Ankerst DP, Wintergerst U, Belohradsky BH, Jansson V. Clinical score for nonbacterial osteitis in children and adults. Arthritis Rheum. 2009;60(4):1152-9. [2] Jansson AF, Grote V; ESPED Study Group. Nonbacterial osteitis in children: data of a German Incidence Surveillance Study. Acta Paediatr. 2011;100(8):1150-7. Disclosure of Interests: None declared